Smart Drug Delivery 2022
DOI: 10.5772/intechopen.100182
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Develop Cyclodextrin-Based Nanosponges for Smart Drug Delivery

Abstract: In recent years, the development of various cyclodextrin (CD)-based nanosponges (NSs) has gained great importance in the controlled and-or targeted release of drugs due to their versatility and simple preparation. In this chapter, an introduction of different administration routes is explained. Further, different ways to obtain CD-NSs and their classification are shown with a brief explanation of the characterization of the inclusion complexes. Finally, illustrative examples in diverse processes or diseases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 97 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…CD-based NSs were synthesized based on previously published protocols [ 34 , 35 , 36 ], and a 1:4 molar ratio of the β-CD: PMDA and β-CD: CDI NSs was utilized [ 20 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…CD-based NSs were synthesized based on previously published protocols [ 34 , 35 , 36 ], and a 1:4 molar ratio of the β-CD: PMDA and β-CD: CDI NSs was utilized [ 20 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…This may be attributable to a slight swelling of the silkMA hydrogel over a 28-day period, which may be limited in pMHMGCL:PCL-silkMA scaffolds due to the presence of covalent bonds between hydrogel with the fibers. 73,74 Furthermore, the tests showed that after 28 days an approximately 3-fold difference in compression modulus value was observed between samples with and without covalent interactions at the interface between the materials. Moreover, as shown in Figure S8, a significant increase in compression modulus is observed in the pMHMGCL-silkMA samples with eqACPCs compared to the cell-free controls, which is in contrast to the samples without the interface interactions (pHMGCL-silkMA) where no significant difference in compression modulus is observed for samples with and without embedded cells.…”
Section: Biological Compatibility and Functionality Of Polymer Blendsmentioning
confidence: 98%
“…As the limited solubility of complexes in aqueous media was considered a potential disadvantage [32,33], new techniques have been developed over time to overcome this impediment [34]. In particular, cyclodextrin-derived nanosponges as transport systems have been obtained through the polycondensation of cyclodextrin molecules with crosslinking agents.…”
Section: Introductionmentioning
confidence: 99%